Integrating Quality Features into Technology Acceptance Model for Examining the Acceptance of Mobile Payment Go-Pay - Djauhari, Medina Juniar; Furqon, Chairul; Sultan, Mokh Adib (Fakultas Pendidikan Ekonomi dan Bisnis, 2020)
Go-Pay was the innovation in Financial Technology offered in efficiency of payment. The main objective of this study was to bring further insights into consumer intentions to use mobile payments Go-Pay it helps improving service quality and increasing user satisfaction of the Go-Jek user. Mobile payment is in a developing stage and consumers are still reluctant and so they hesitate to use mobile payment. Data is collected from Go-Jek user who have used Go-Pay as mobile payment systems in Bandung city. A survey study with the SEM analysis of 200 participants, with four out of six hypothesis are supported. Research results demonstrate that there are significant relationships between service quality and intention to use, there is not significant relationship between perceived ease of use, perceived usefulness to intention to use mobile payment Go-Pay.Â Keyword. Quality Technology Acceptance Model (QTAM); Intention to Use; Structural Equation Model;